2001
DOI: 10.1074/jbc.m104516200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glutathione Depletion on Antitumor Drug Toxicity (Apoptosis and Necrosis) in U-937 Human Promonocytic Cells

Abstract: Treatment with the DNA topoisomerase inhibitors etoposide, doxorubicin, and camptothecin, and with the alkylating agents cisplatin and melphalan, caused peroxide accumulation and apoptosis in U-937 human promonocytic cells. Preincubation with the reduced glutathione (GSH) synthesis inhibitor L-buthionine-(S,R)-sulfoximine (BSO) always potentiated peroxide accumulation. However, although GSH depletion potentiated the toxicity of cisplatin and melphalan, occasionally switching the mode of death from apoptosis to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(110 citation statements)
references
References 57 publications
5
104
1
Order By: Relevance
“…If this was the case we could predict a similar potentiation of apoptosis when the phorbol ester is used in combination with other GSH-sensitive agents but probably not with GSH-insensitive drugs. Earlier observations indicated that GSH depletion enhanced the toxicity of the heavy metal cadmium (43, 44) but did not affect the toxicity of anti-DNA topoisomerase drugs in myeloid cells (29,45). Hence, we decided to compare the effect of BSO and TPA on U-937 cells treated with cadmium chloride (CdCl 2 , 40 M) and with the antitumor anti-DNA topoisomerase drugs etoposide (0.5 M), camptothecin (50 nM), and doxorubicin (0.5 M).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If this was the case we could predict a similar potentiation of apoptosis when the phorbol ester is used in combination with other GSH-sensitive agents but probably not with GSH-insensitive drugs. Earlier observations indicated that GSH depletion enhanced the toxicity of the heavy metal cadmium (43, 44) but did not affect the toxicity of anti-DNA topoisomerase drugs in myeloid cells (29,45). Hence, we decided to compare the effect of BSO and TPA on U-937 cells treated with cadmium chloride (CdCl 2 , 40 M) and with the antitumor anti-DNA topoisomerase drugs etoposide (0.5 M), camptothecin (50 nM), and doxorubicin (0.5 M).…”
Section: Resultsmentioning
confidence: 99%
“…Measurement of GSH Levels-The total cellular GSH content was determined by fluorometry after cell loading with monochlorobimane following the previously described procedure (29).…”
Section: Measurement Of Caspase-3 Activity-samples Of 4 ϫ 10mentioning
confidence: 99%
“…For example VP16, or etoposide, is a topoisomerase II inhibitor; however, there are reports in the literature of VP16-induced cell death being mediated through pathways independent of topoisomerase II inhibition, but dependant on ROS production. 4,6 It is likely that the generation of ROS by cytotoxic drug treatment of cells results in nonenzymatic protein modifications that may play an important role in the early stages of apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…The response to H 2 O 2 was also inhibited by about 50% following culture of U937 cells for 24 h in the presence of BSO (Fig. 2C), which depletes cells of GSH by inhibiting ␥-glutamylcysteine synthetase (32). In contrast, BSO had no effect on the stimulatory effect of PMS on 5-oxo-ETE formation.…”
Section: Oxidant Stress Enhances the Synthesis Of 5-oxo-ete-asmentioning
confidence: 83%